The tribalism impediment on the enforcement of international arbitral awards in Yemen - Bawazir, Omar Saleh Abdullah (Future Academy, 2018)
Tribal influence on the ability of the courts to enforce international arbitral awards (IAA) in Yemen is primarily considered in this research. Especially, Yemen is categorized as one of the worst countries suffering from tribalism worldwide. The study employed a doctrinal approach and socio-legal research method by applying data collected through library while the doctrinal legal research applies legal case studies. Additionally, the study collects data through face to face semi-structured interviews with experts. The data were analysed by using critical analysis. It was found that tribalism is a big obstacle to the enforcement of IIA in Yemen because tribal leaders interfere in the judicial process to protect people from their own tribes. This study helps to legislate stricter laws to combat the tribal interference in the affairs of the judiciary and coerce the tribes to comply with court orders. Also, it contributes to the knowledge of the extent of the tribalism influence on enforcement of IAA as the researcher has not found previous studies focusing on the impact of tribalism.